Transcription Factor TCF4 Maintains the Properties of Human Corneal Epithelial Stem Cells123. (22nd March 2012) - Lu, Rong; Qu, Yangluowa; Ge, Jian; Zhang, Lili; Su, Zhitao; Pflugfelder, Stephen C.; Li, De‐Quan
Abstract: TCF4, a key transcription factor of Wnt signaling system, has been recently found to be essential for maintaining stem cells. However, its signaling pathway is not well elucidated. This study was to explore the functional roles and signaling pathway of TCF4 in maintaining adult stem cell properties using human corneal epithelial stem cells as a model. With immunofluorescent staining and real‐time polymerase chain reaction, we observed that TCF4 was exclusively expressed in the basal layer of human limbal epithelium where corneal epithelial stem cells reside. TCF4 was found to be well colocalized with ABCG2 and p63, two recognized epithelial stem/progenitor cell markers. Using in vitro culture models of primary human corneal epithelial cells, we revealed that TCF4 mRNA and protein were upregulated by cells in exponential growth stage, and RNA interference by small interfering RNA‐TCF4 (10‐50 nM) transfection blocked TCF4 signaling and suppressed cell proliferation as measured by WST‐1 assay. TCF4 silence was found to be accompanied by downregulated proliferation‐associated factors p63 and survivin, as well as upregulated cyclin‐dependent kinase inhibitor 1C (p57). By creating a wound healing model in vitro, we identified upregulation and activation of β‐catenin/TCF4 with their protein translocation from cytoplasm to nuclei, as evaluated by reverse transcription‐quantitative real‐time polymerase chain reaction, immunostaining, and Western blotting. Upregulated p63/survivin and downregulated p57 were further identified to be TCF4 downstream molecules that promote cell migration and proliferation in wound healing process. These findings demonstrate that transcription factor TCF4 plays an important role in determining or maintaining the phenotype and functional properties of human corneal epithelial stem cells. STEM CELLS 2012; 30:753–761